What does it mean to be a 'national' gallery when the notions of 'nation' transform radically?: An analysis of the Iziko South African National Gallery's practices and policies in historical contexts - Barben, Marc Walter (Michaelis School of Fine Art, 2015)
Includes bibliographical references.